Mastery of information technology among Malay language students - Jusoh, Zuraini (Human Resource Management Academic Research Society, 2020)
Information and communication technology skills are some of the most important components that are emphasized y employers today. This rapid technological development makes the curriculum in institutions of higher learning to apply technological elements in teaching and learning. Students are not left ehind in the field of language to enale them to compete in the career market after completing their studies. To that end, a survey using a questionnaire was conducted to identify the level of information and communication technology skills among students in the field of language. A total of 30 samples from 9(30.0%) men and 21(70.0%) were female students in the fifth semester to the final semester of the achelor of Arts (Malay Language and Linguistics). In total, 11(36.7%) students are moderately skilled and 19(63.3%) are highly skilled in information and communication technology skills. Most of the students surveyed also spend more than seven hours surfing the Internet which is usually rowsed through their respective smartphones. Usually, these students surf the Internet to access email, for entertainment and curiosity.